Fiber Diet-Mediated Increases in Short Chain Fatty Acids Alleviate Western Diet Induced Metabolic Dysfunction. (7th June 2021) - Priyadarshini, Medha; Khan, Md Wasim; Xu, Kai; Yeh, Jade; Wicksteed, Barton; Layden, Brian
Abstract: Objectives: Short chain fatty acids (SCFAs), which are gut microbial fermentation byproducts with suggested positive health effects, have emerged as a therapeutic modality against metabolic diseases like obesity and type 2 diabetes. Alluringly, in vivo SCFA levels are easily modifiable by consumption of fermentable fibers (FF). Most rodent studies on dietary FF supplementation report terminal increased cecal/fecal SCFA levels but the time course of this increase remains elusive. Also, there is limited information on the effect of this sustained SCFA increase on physiology. Thus, we investigated dietary FF-dependent temporal increases in plasma SCFA levels and its metabolic effects on a western diet (WD) mouse model. Methods: C57BL/6J male mice (age 10 weeks) were fed test diets for 8 weeks. In Phase I, to establish time-course of plasma SCFA increase, mice were fed the following isocaloric diets: control (low fat + 0% FF); WD; control + 20% FF, where FF was fructooligosaccharides (FOS), inulin (In), guar gum (GG) or pectin (Pec). In Phase II mice were fed a control diet, or a WD with or without 20% FOS, Pec or GG. End points were weekly plasma SCFAs (by MS/MS), body weight, random glucose and insulin, and at the end of experimental period body fat composition and metabolic tests. Results: Phase I. Compared to control, WD lowered while FF induced significant increases in total plasma SCFAs (FOS, Pec, GG > In) in a time dependent manner that plateaued beyond 2 weeks. All FF increased propionate and acetate but not butyrate. Phase II. WD caused metabolic dysfunctions (increased body weight and fat mass; glucose intolerance; insulin resistance; P < 0.0001 by two-way ANOVA) that were alleviated in mice fed FF enriched WD (Pec = GG > FOS). Compared to WD, food intake was similar except high in the WD-Pec group, while WD-Pec and GG showed higher energy expenditure. All 3 plasma SCFAs were significantly higher in all WD-FF groups. FF supplementation of the control diet showed no significant difference compared to control. Conclusions: We conclude that: 1) FF feeding induced SCFA production reaches saturation within 2 weeks, suggesting selection of specific gut bacterial features; and 2) all FFs were protective from weight gain and its metabolic consequences. Funding Sources: 2R01 DK104927 (NIH/NIDDK) Layden.